Dampak Berjudi dalam Pandangan Islam - Muhammad Reyhan Givani Hendrasjah; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss the negative impact of gambling behavior in the Islamic view. The method used in this research is qualitative through literature study. The results and discussion of this study are that in Islam gambling is described as "a transaction between two parties in the ownership of an object or service that helps and benefits one party and harms another party by tying the transaction to certain actions or events. Another term gambling refers to any game which involves betting in the form of money, goods, etc. The conclusion of this study is that gambling does not contribute to economic growth because it produces no output other than the transfer of money and products between individuals. Gambling does not drive productivity, on the contrary, it is a waste of energy and time for those involved in therein and this has been confirmed in the Qur'an.